In-vitro assessment of crossbred buck fertility - KALE, M M; MANIK, R S; TOMER, O S (The Indian Journal of Animal Sciences, 2013)
A study was conducted on 10 crossbred bucks (aging 2G to 50 months) to evaluate their fertility status on the basis of semen quality and hypo-osmotic swelling test (HOS), cervical mucus penetration test (CMPT) and resistance to 1% NaCI solution during 3 seasons (hot-dry, hot-humid and cold-humid). Collections (150) were made and the quality of semen was evaluated using standard procedures. The analysis of semen revealed that, revealed that, resistance value was significantlyÂ  (P